Key nutritional considerations for youth winter sports athletes to optimize growth, maturation and sporting development - Hannon, M. P.; Flueck, J. L.; Gremeaux, V.; Place, N.; Kayser, B.; Donnelly, C. (Frontiers in Sports and Active Living, 2021)
Despite a wealth of sport nutrition guidelines for adult athletes, there are currently no nutrition guidelines for youth winter sports athletes. Whilst it may be pragmatic to apply nutrition guidelines for adult athletes to youth winter sports athletes, it is inappropriate. Due to a paucity of research on youth athletes, it is impossible to provide evidence-based guidelines for this population, so careful extrapolation from the theoretical and practical considerations that apply to other athletic groups is necessary. Youth winter sport athletes undergo rapid biological growth and maturation which influences their nutritional requirements. A varied and balanced diet that ensures sufficient energy availability for optimal growth and maturation as well as sporting performance is the cornerstone of youth athlete nutrition and should also allow for youth athletes to meet their micronutrient requirements. In some cases, micronutrient status (e.g., vitamin D and iron) should be monitored and optimized if appropriate by a medical professional. Dietary supplement use is prevalent amongst youth athletes, however is often unnecessary. Education of youth athletes, their parents and coaches on best nutritional practices as well as the risks associated with dietary supplements is vital for their long-term athletic development. Further research in youth winter sports athletes across different stages of growth and maturation competing in a variety of sports is urgently required in order to inform nutritional guidelines for this population.